Issues In Teaching Speaking In Bilingual Class - Mildan Arsdan Fidinillah (Scope : Journal of English Language Teaching, 2019)
Students who study in bilingual class are expected to have the ability of speaking English as well as Indonesian. This study looks at the learning steps in teaching speaking English in bilingual class that claimed their students are able to speak fluently in English within one year. The research data was taken from two bilingual classes at Madrasah Ibtidaiyah Negeri (MIN) Ciputat, South Tangerang City, Banten. The sample of this study were 20 bilingual class students from class 6. The instruments of the research are questionnaire and class observation. Questionnaire is given to the teachers related to their methods in teaching speaking, class observation is done to see the ability of students in speaking. This research is limited only to the teaching steps of English speaking in the bilingual class. The results of this study indicates that by practicing the cluster method carried out by the teacher, the students' speaking skills improved significantly in a short time  Key Words: Bilingual, monoligual, literacy instruction,  RINGKASAN Siswa yang belajar dikelas bilingual ddiharapkan mempunyai kemampuan berbicara bahasa Inggris sebaik bahasa Indonesia. Penelitian ini mencari tahu langkah-langkah pembelajaran yang terkait dengan kemampuan berbicara bahasa Inggris di kelas bilingual yang mengklaim siswanya dapat lancer berbicara bahasa Inggris dalam waktu satu tahun. Data-data penelitian  diambil dari dua kelas bilingual di Madrasah Ibtidaiyah Negeri (MIN) Ciputat Kota Tangerang Selatan Banten. Sampel penelitian ini adalah 20 siswa kelas bilingual yang berasal dari kelas 6. Instrument dari penelitian ini adalah angket dan observasi kelas. Angket diberikan kepada guru untuk melihat metode mengajar yang terkait dengan kemampuan berbicara, observasi kelas dilakukan untuk melihat sejauh mana kemampuan berbicara bahasa Inggris siswa. Penelitian ini dibatasi hanya pada langkah-langkah pengajaran berbicarabahasa Inggris dikelas bilingual. Hasil penelitian ini menunjukan bahwa dengan mempraktekan metode kluster yang dilakukan oleh guru, kemampuan berbicara siswa dapat meningkat secara signifikan dalam waktu yang relatif singkat    Kata Kunci: Dwi bahasa, bahasa tunggal, instruksi lisan